Pengaruh Green Percevied Value, Green Product Innovation, Green Self Identitiy, Brand Credibility Terhadap Green Purchase Intention Melalui Green Brand Equity Pada Produk Skin-Care Korea Di Indonesia - Alvin Alvin (Universitas Tarumanagara, 2019)
The purpose of this study was to analyze the influence of Green Perceived Value, Green Product Innovation, Green Self Identity, Brand Credibility to Green Purchase Intention through Green Brand Equity on Skin Care Korean Products in Indonesia. Respondents in this research is done by taking a sampling with purposive judgement selection on Innisfree and Nature Republic customer in Indonesia. The method is carried out in the form of survey method with the dissemination of questionnaires with population numbers 250 people. In conducting this research, the author uses the validity test, reability, , estimation model test, structural model test, classic t test. In conducting this research, the author uses the SPSS application version 17.0 and Lisrel 9. The results of this research show that the Green Perceived has no effect on Green Purchase Intention, Green Perceived Value has no effect on Green Brand Equity, Green Product Innovation has no effect on Green brand Equity, Green Self Identity affect positively on Green Brand Equity, Brand Credibility affect positively on Green Brand Equity, Brand Credibility affect positively on Green Purchase Intention, Green Product Innovation hasn’t indirect effect on Green Purchase Intention, Green Self Identity has indirect effect on Green Purchase Intention